Application of Governance Principles in Faculties of Education of Arab Universities: Requirements and Aspirations - Hussen, Bannaga Taha Al-Zubair; Onia, Saifaldin Idris (PT. Riset Press International, 2024)
Governance of higher education institutions covers many areas including human resource management, funding, and education quality as well as assurance internationalization, academic and scientific planning that enhances transparency, accountability and participation. Therefore, this study aimed to identify the requirements for applying the principles of governance in the faculties of education at Arab universities. The study followed the qualitative and interpretive method, as well as analyzing the content of previous studies related to the study. The study reached that the faculties of education in Arab universities actually apply to a moderate degree the principles of governance in their management, as well as self-monitoring, development and sustainability. The study recommends that faculties of education should issuing regulations and legislation regarding standards and principles of governance in faculties of education in Arab universities, and obligating departments and councils to work with them. Besides, establishing independent committees within the faculties of education to follow up and evaluate the application of governance principles.